STUDY ON THE VARIETIES OF PAROTTAS CONSUMED AND THEIR ADVERSE EFFECTS ON THE PEOPLE - Dr. M.S. Rabha; A. Marithangam; S.Charu Nivedha (The Bioscan, 2026)
Parotta, a popular South Indian flatbread known for its flaky layers and delicious taste, has gained widespread popularity in recent years. However, the consumption of parottas, especially prepared with different ingredients and cooking methods, may have potential adverse effects on the health of individuals. This study aims to investigate the varieties of parottas consumed and their adverse effects on the people of Thoothukudi, a coastal city in Tamil Nadu, India. The study employed a mixed-methods approach, including surveys, dietary assessments, and health screenings, to gather comprehensive data on parotta consumption patterns and associated health outcomes among the residents of Thoothukudi. Through a survey, it is found that, types of parottas preferred plain parotta, accompanying chicken gravy as a side dish, and cooking methods preferred pan fried was mostly preferred by the people. The study reveals a correlation between excessive consumption of types of parottas and adverse health effects such as obesity, diabetes and digestive disorders among the population.